Peran Layanan Digital dalam Perbankan Syariah dan Strategi Mitigasi Risiko Siber - Intan Putri Nurkhanifah; Vina Melinda; Vitakhil Ilmiyah; Binti Nur Asiyah (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology has driven significant transformation in the banking sector, including Islamic banking which is now adopting digital services to improve efficiency and quality of service. The main issues raised in this study are how digital services play a role in supporting Islamic banking operations and what strategies are implemented to mitigate the accompany cyber risks. This study aims to analyze the contribution of digital services to Islamic banking performance and identify risks and mitigation strategies implementd in dealing with cyber threats. The method used is a qualitative study with an analytical approach through literature review, case studies, and semi-structured interviews with Islamic banking practitioners. The results of the study show that digital services play an important role in increasing financial inclusion, operational efficiency, and customer satisfaction. However, the use of digital technology also presents risks such as cyber attacks, data leaks, and regulatory uncertainty. The mitigation strategies identified include trengthening IT governance, implementing a multilayered security system, human resource training, and compliance with OJK regulation and sharia principles. In conclusion, digital service are a strategic asset in the developmentof Islamic banking, but require careful cyber risk governance to maintain trust and service sustainability.